2009
DOI: 10.3945/jn.108.094052
|View full text |Cite
|
Sign up to set email alerts
|

Iron Loading Increases Ferroportin Heterogeneous Nuclear RNA and mRNA Levels in Murine J774 Macrophages

Abstract: The transmembrane protein ferroportin is highly expressed in tissue macrophages, where it mediates iron export into the bloodstream. Although ferroportin expression can be controlled post-transcriptionally through a 5' iron-responsive element in its mRNA, various studies have documented increased ferroportin mRNA levels in response to iron, suggesting transcriptional regulation. We studied the effect of iron loading on levels of macrophage ferroportin mRNA, as well as heterogeneous nuclear RNA (hnRNA), the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 40 publications
5
41
0
2
Order By: Relevance
“…The steady-state level of an hnRNA of a given gene is widely believed to reflect the transcription rate of that gene and is often used as a surrogate for the nuclear run-on assay (3,7,8,14,26). In this study, we examined the effect of chronic alcohol use on the level of expression for THTR1 (Slc19a2) and THTR2 (Slc19a3) hnRNA in rat kidneys.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The steady-state level of an hnRNA of a given gene is widely believed to reflect the transcription rate of that gene and is often used as a surrogate for the nuclear run-on assay (3,7,8,14,26). In this study, we examined the effect of chronic alcohol use on the level of expression for THTR1 (Slc19a2) and THTR2 (Slc19a3) hnRNA in rat kidneys.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the effect of chronic alcohol feeding on the level of expression of hnRNA of THTR1, THTR2, and TPKase, total RNA [treated with DNase I (1 g RNA/unit; Invitrogen) to avoid genomic DNA presence during the amplification process] was isolated from the kidneys of alcohol-fed rats and their pair-fed controls as described previously (3,8,14). DNase I-treated RNA was then reverse transcribed with the random hexomer as described above (Invitrogen).…”
Section: Materials [mentioning
confidence: 99%
“…6 In both J774 cells and Caco cells, the increase in Fpn expression resulted in increased iron export. What is unclear, however, is the physiologic function of transition metal-induced expression of Fpn.…”
Section: Introductionmentioning
confidence: 99%
“…Fpn, however, can be expressed on a wide variety of other cell types in response to heme 3,4 or iron. [5][6][7] Iron can regulate Fpn expression through transcriptional and translational mechanisms. Ferroportin1 (FPN1), the gene that encodes Fpn, contains a 5Ј iron-responsive element (IRE), which places its translation under the control of iron regulatory proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Hepcidin, the key mediator of iron metabolism, causes internalization and degradation of Fpn-1, resulting in a reduction of iron export with a resultant increase in cellular iron. 2,18 Several studies have also demonstrated a direct regulatory effect of iron, 19,20 IRP1 and IRP2 on the Fpn-1 gene expression. 21 In addition, a recent study identified and characterized two isoforms of Fpn-1 (Fpn-1a and Fpn-1b), which differ from each other as a result of the presence or lack of an iron regulatory element.…”
mentioning
confidence: 99%